Synthesis and Characterization of Veronica beccabunga Green Synthesized Silver Nanoparticles for The Antioxidant and Antimicrobial Activity - Hamdullah SEÇKİN; İsmet MEYDAN (Türkiye Tarımsal Araştırmalar Dergisi, 2021)
The use of nano-agents in the healthcare field is an important alternative in reducing the increasing pathogen resistance. One of the main purposes of the nano mechanism is that the secondary metabolites produced naturally in plants become more effective through metals. Silver (Ag) nanoparticles were obtained by green synthesis using Veronica beccabunga plant extract and AgNO3 in our study. Scanning electron microscopy was used for SEM, SEM / EDX images of synthesized silver nanoparticles. The interaction of V. beccabunga with Ag was explained by X-ray diffraction (XRD) analysis. The characterization process was performed using an ultraviolet-visible (UV-vis) spectrophotometer and Fourier converted infrared spectroscopy (FT-IR). It was determined that silver nanostructures have an important antioxidant potential as a result of 2,2-difenil-1-pikrilhidrazil (DPPH) analysis. The antimicrobial activity of synthesized metal nanoparticles was investigated, against some pathogens causing disease in humans, by the disk diffusion method. Ag NPs /Vb has been found to have antibacterial effects against Bacillus subtilis ATCC 6633, Escherichia coli ATCC 25952, Pseudomonas aeruginosa ATCC 27853 microorganisms. In our current study, Ag NPs / Vb appears to provide a remarkable effect for its use in medicine, pharmacology.